ELUCIDATION OF CONFUCIAN HUMANISM AS AN ANTHROPOCOSMIC HUMANISTIC PHILOSOPHY - Raj, S. Mohan; V, Sunitha. (International Journal of Psychosocial Rehabilitation, 2020)
Confucianism is humanism as it is centred on the advancement of human, as a collective community. The philosophy much inclines towards strict convictions and leans towards religious beliefs. The goals are of Yin, Yang, Tian, and ceremony. The significant thoughts on identifying Confucianism as a humanistic approach are based on the ideals of the sage-thinker which are marked as four ideals. They are Ren, Li, Yi, and Zhi. These ideals refer to the humankind, custom appropriateness, proper conduct, and practical knowledge. The other ideals supporting humanism includes Renxing (human nature and humanity), change through contemplation, and reflection of self. This paper centres essentially on the ideas of Confucianism in the two books the Analects and Mengzi. It is Weiming (1999) who put forth Confucianism as anthropocosmic. This thinking of anthropocosmic blooms out of the Confucian accentuation on ideal harmony between Tian, nature, and Ren the people, the sequel between Tian and Ren, and the link amid Tian, Ren, and Earth. It is anthropocosmic too, with its worth hypothesis accounts for itself from cosmological, moral, and spiritual perspectives. Confucianism is not a strict way of thinking, yet it is a strict humanism with religious incline.